Super Bowl Ads & Firm Value Enhancement - Hofer, Ashley; Rozumalski, Dan; Coulombe, Cory (My University, 2011)
As advertisers spend millions of dollars for commercials on Super Bowl Sunday, it is becoming increasingly important to produce returns on these pricey investments. This study compared the stocks of publicly traded Super Bowl advertising companies to the S&P 500 as one way to examine Super Bowl advertising effectiveness.
Color poster with text, images, and graphs.
Keywords: Super Bowl--Advertising--Evaluation; Super Bowl--Economic aspects; Television advertising--United States--Longitudinal studies; Stocks--Prices--Research; Posters